Distribution System Operation: Flexibility Services Summary of Key Outputs From the Open Networks Programme - Aithal, Avinash; Wainwright, Andrew; Atkins, Steve; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book is a coherent and accessible source of knowledge on flexibility services for energy. Local flexibility services are a commercial mechanism which allows participants to be renumerated for delivering a change in their usual power use, in real time or in response to prior request from the Distribution System Operators (DSOs) to help manage network congestion. Summarising key outputs from the Energy Networks Association$1 (Bs (ENA) Open Networks Programme, the book traces the evolution of local flexibility markets from 'Proof of Concept' to 'Business as Usual'. The book presents detailed technical and organisational insights from the development of local flexibility markets, focusing on inception, standardization, simplification, and transparency in decision-making across GB DSOs and interactions with the National Energy System Operator (NESO). Readers will find valuable comparisons of implementation approaches by different network companies, highlighting technical nuances and best practices. Ideal for researchers, energy professionals, and policymakers, this book provides a critical resource for understanding the complexities and opportunities of flexibility services in energy systems. Whether you are involved in energy management, policy development, or academic research, this book offers essential insights into the future of energy flexibility and grid management. .s
Foreword -- Preface -- ENA members -- Contributions and Acknowledgements -- Section A: Background and Context -- 1. Need for Distribution System Operation -- 2. Market Principles -- Section B: Local Flexibility Services -- 3. Flexibility Products -- 4. Forecasting and Development Plans (Pre-procurement) -- Section C: Deployment of Flexibility Services -- 5. Procurement Process -- 6. Dispatch of Flexibility Services -- 7. Settlement -- Section D: Interactions Across Markets -- 8. Interoperability of Flexibility Dispatch Systems -- 9. Flexible Connections and Flexibility Services -- 10. Conflict management (Primacy Rules) -- 11. Stackability of Flexibility Services -- Section E: Additional Resources -- 12. Carbon Impact Assessment of Flexibility Service -- 13. Industry Jargon Buster -- 14. Reference -- 15. Appendix.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Electric power distribution; Power resources; Renewable energy sources; Mathematical optimization; Energy Grids and Networks; Natural Resource and Energy Economics; Renewable Energy; Optimization